2018
DOI: 10.21595/jme.2018.20028
|View full text |Cite
|
Sign up to set email alerts
|

An approach to 24-hour electrocardiogram monitoring in sheep experimental model

Abstract: Sheep could be an excellent research subject for large animal experimental studies because of their heart structure and physiology have a lot similarity to the human. Long term ECG monitoring is a convenient tool for human and possibly veterinary clinical practice and research. Continuous ECG recording can be used to monitor and evaluate body physiological responses in various experimental conditions. Experience on sheep ECG monitoring techniques is sparse and mostly focused on short term ECG recordings. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Long-term ECG monitoring is very important in veterinary clinical practice to diagnose the health condition of animals. Studies have been performed on sheep [ 113 ], dogs [ 114 ], buffaloes [ 115 ], rabbit [ 33 ] and horses [ 116 ]. Conventionally, crocodile clamps electrodes together with adhesive gel are used for ECG measurements on animals.…”
Section: Textile Electrodes In Veterinary Ecg Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term ECG monitoring is very important in veterinary clinical practice to diagnose the health condition of animals. Studies have been performed on sheep [ 113 ], dogs [ 114 ], buffaloes [ 115 ], rabbit [ 33 ] and horses [ 116 ]. Conventionally, crocodile clamps electrodes together with adhesive gel are used for ECG measurements on animals.…”
Section: Textile Electrodes In Veterinary Ecg Monitoringmentioning
confidence: 99%
“…Recorded ECG signal quality is affected by motion artifacts and remains one of the major problems which arise due to the absence of uniform skin–electrode contact, the detection of muscle movement, higher contact impedance, and unwanted wire movement during acquisition [ 113 , 120 ]. Motion artifacts can be minimized via proper skin preparation that could help to reduce contact impedance and by using modified electrodes.…”
Section: Textile Electrodes In Veterinary Ecg Monitoringmentioning
confidence: 99%
“…Scheer et al (2005) have suggested that small ruminants like sheep are an ideal animal for Holter-monitoring, since they are big enough, are quiet and have non-destructive behaviour. Furthermore, Kviesulaitis et al (2018) stated that sheep could be an excellent research subject for large animal experimental studies owing to their heart structure and physiology, which have considerable similarity to those of humans.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Kviesulaitis et al. (2018) stated that sheep could be an excellent research subject for large animal experimental studies owing to their heart structure and physiology, which have considerable similarity to those of humans.…”
Section: Discussionmentioning
confidence: 99%
“…In ungulates, Purkinje fibers, a major component of the mammalian ventricular electrical conduction and propagation system, form subendocardial and intramural networks that extend excitation across the ventricular walls. The morphology and function of the Purkinje cell network are reflected in the ECG electrical axis of the heart in ungulates (Detweiler, 2010) and can lead to larger and longer T waves, with relatively smaller QRS complexes as seen in sheep (Kviesulaitis et al, 2018) and pig (Hamlin, 2010). When using implantable biologgers (Graesli et al, 2020a) or sensors attached to the skin (Kviesulaitis et al, 2018), T waves might be detected by the algorithm as ventricular depolarization (QRS complex), leading to double counting of heartbeats.…”
Section: Biologger Use and Accuracymentioning
confidence: 99%